Solbergsparken - Svantesson, Emelie (2021)
“For over a thousand years, Solberget has proudly guarded life in Växjö. The famous mountain carries a long and captivating history. With the stories of that time in mind, a new grand story is born. A story about life on the mountain and the people who now make the place to their home”* (Bergön, 2018, p.3). Solberget has a long history and important natural and cultural values (Åkerberg, 2010), but when a new 19-storey residential building was completed in 2018 at the top of the mountain (Bergön, 2018), the park’s character, conditions and problems changed significantly. The main perceived problem that the residential building has caused is the diffuse boundary between private, semi-private and public. According to Boverket (2008) the ambiquity of the zones are common around houses like the new residential building. Clearness of the zones is described as extra important around the type of residential building and the feeling of knowing which people are moving in an area is important for people’s well-being, Boverket (2008) writes. “The outdoor environment around the residential building must be designed with great care with regard both to future residents in the area but also to the public who visit the park”1 * (Växjö kommun, 2013, p.5). In addition to the value of clarifying the zones, the new conditions place greater demands on safety and accessibility in the area. The feeling of safety and accessibility are two basic preconditions for people to want and be able to stay in the area (Boverket, 2008). At present, both aspects are insufficient. The rocky ground creates boundaries, obstacles and makes it difficult to get from different directions. Lighting is almost non-existent, the zones are diffuse and the back of the area meets the adjacent school’s storage and containers. * The quote is freely interpreted and translated by the author / Citatet är fritt översatt av författaren. The project includes the concepts of private, semi-private and public, as well as safety and accessibility through literature, interviews, observations and sketching. Safety and accessibility act as pillars and clarity of the currently problematic and diffuse zones as the main issue. The concept is formulated according to the area’s most current problems. As a critical and also as an inspiring aspect in the process a reference study has been made where a number of places have been visited. The places are linked to the problems at Solberget and the formulated concept. Based on literature, analyzes, interviews, site visits and reference sites, a design proposal has finally been formulated. Eight tools have been developed as a basis for the design proposal. The tools sightlines, connected, characters and boundaries are linked to what is to be achieved and the tools paths, materials, markers and vegetation describe how. New continuous paths, development of the main path, extension of the meadow land, sightlines towards characteristic elements and recurring materials and color have contributed to creating a well-connected and clear public park. Markers in the form of trees and shrubs, a low mound and different characters of vegetation contribute to creating a clearer boundary between the semi-private zone and the public. Clearer zones, a more planned design of the park, lighting, stairs and paths contribute to a safer and more accessible area. The intention and goal of the new proposed design for Solberget has been to create a clear, safe and accessible park where people can and want to stay.